Comparison of visual motor integration, participation and hand skills in children with and without type 1 diabetes - Kılıçöz, Mehtap; Kutlutürk Yıkılmaz, Seval; Yüksel, Ayşegül; Kaya Kara, Özgün (SAGE Publications Inc, 2022)
Our aim in this study was to compare hand skills, visual-motor integration ability, and participation in daily living activities of children with and without Type 1 diabetes (T1DM). In this prospective cross-sectional study, we included 44 children withT1DM (17 males, 27 females; aged 8-12 years) and a control group of 45 healthy age-matched children without T1DM (22 males, 23 females). We compared group scores on the Jebsen-Taylor Hand Function Test (JTHFT), the Beery-Buktenica Developmental Visual Motor Integration Test (Beery VMI), and on the Participation and Environment Measure - Children and Youth (PEM-CY). The JTHFT and Beery VMI scores of children with T1DM were significantly lower than those of the control group (p <= 0.005); on the PEM-CY, children with T1DM were found to have more barriers in the community than controls. Relative deficits in hand skills and visual motor integration of children with T1DM should be managed with greater attention and assistance.
Keywords: Hand Skills; Participation; Type 1 Diabetes; Visual-Motor Integration